Molecular Pathways: Targeted α-Particle Radiation Therapy - Baidoo, Kwamena E. (2012)
An α-particle, a (4)He nucleus, is exquisitely cytotoxic, and indifferent to many limitations associated with conventional chemo- and radiotherapy. The exquisite cytotoxicity of α radiation, the result of its high mean energy deposition (high linear energy transfer, LET) and limited range in tissue, provides for a highly controlled therapeutic modality that can be targeted to selected malignant cells (targeted α-therapy (TAT)) with minimal normal tissue effects. There is a burgeoning interest in the development of TAT that is buoyed by the increasing number of ongoing clinical trials worldwide. The short path length renders α-emitters suitable for treatment and management of minimal disease such as micrometastases or residual tumor after surgical debulking, hematological cancers, infections, and compartmental cancers such as ovarian cancer or neoplastic meningitis. Yet, despite decades of study of high-LET radiation, the mechanistic pathways of the effects of this modality remain not well defined. The modality is effectively presumed to follow a simple therapeutic mechanism centered on catastrophic double strand (ds) DNA breaks without full examination of the actual molecular pathways and targets that are activated that directly impact cell survival or death. This Molecular Pathways article provides an overview of the mechanisms and pathways that are involved in the response to and repair of TAT induced DNA damage as currently understood. Finally, this article highlights the current state of clinical translation of TAT as well as other high-LET radionuclide radiation therapy using α-emitters such as (225)Ac, (211)At, (213)Bi, (212)Pb and (223)Ra.